1996
DOI: 10.1074/jbc.271.3.1669
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biophysical Comparison of Native and Chemically Synthesized Phospholamban and a Monomeric Phospholamban Analog

Abstract: Phospholamban (PLB) was rapidly isolated from canine cardiac sarcoplasmic reticulum using immunoaffinity chromatography and prepared by solid phase peptide synthesis. The two proteins are indistinguishable when analyzed by SDS-polyacrylamide gel electrophoresis and exhibit pentameric oligomeric states. They are similarly detected on Western blots, are phosphorylation substrates, have identical amino acid compositions that directly reflect their predicted values, yield the same internal amino acid sequences upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…3) and in SDS-polyacrylamide gels according to Laemmli (30) (data not shown), PLB-(24 -52) showed the typical monomer-pentamer pattern, which also has been observed for native PLB (31). Complete dissociation of pentameric PLB-(24 -52) on SDS gels required boiling in the presence of high concentrations of SDS (4 -5%) at low protein concentrations, as is the case for native PLB (32).…”
Section: Oligomerization In Sds and Nonionic Detergents-inmentioning
confidence: 54%
“…3) and in SDS-polyacrylamide gels according to Laemmli (30) (data not shown), PLB-(24 -52) showed the typical monomer-pentamer pattern, which also has been observed for native PLB (31). Complete dissociation of pentameric PLB-(24 -52) on SDS gels required boiling in the presence of high concentrations of SDS (4 -5%) at low protein concentrations, as is the case for native PLB (32).…”
Section: Oligomerization In Sds and Nonionic Detergents-inmentioning
confidence: 54%
“…Alternatively, PLB has been prepared by chemical synthesis using standard solid-phase peptide synthesis and purification in organic solvents (69,70). In addition, this approach gives the opportunity to synthesize site-specific isotopically labeled peptides and proteins (30,59,71).…”
Section: Synthesis and Purification Of Plbmentioning
confidence: 99%
“…In earlier studies we showed that the PLN cytoplasmic interaction site is formed by charged and hydrophobic amino acids 1-20 (6), while the complementary SERCA2a interaction site consists of amino acids Lys-Asp-Asp-Lys-Pro-Val 402 (7). In a later evaluation of potential transmembrane interaction sites (8), we coexpressed SERCA2a with PLN transmembrane sequences 31-52 (PLN domain II) or with PLN domain II constructs to which NH 2 -terminal, cytoplasmic epitopes such as PLN [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or hemagglutinin were fused. We found that the inhibitory interaction site lies entirely in the transmembrane sequences of PLN and SERCA2a, but can be modulated, through long range interactions, by the noninhibitory cytoplasmic interaction site.…”
Section: Phospholamban (Pln)mentioning
confidence: 99%
“…Gain of function was first observed in studies involving coexpression of SERCA2a with PLN domain II constructs to which NH 2 -terminal, cytoplasmic epitopes such as PLN [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or hemagglutinin were fused (8). An examination of Fig.…”
Section: Phospholamban Activation 15063mentioning
confidence: 99%
See 1 more Smart Citation